Aplicação da secagem em silagem ácida de tambatinga (Colossoma macropomum X Piaractus brachypomus) - Pires, Letícia Gabriela Pozzer (2018)
The residues generated by industries or fish processing refrigerators are a problem of environmental pollution, an alternative and promising use of this waste is in dehydrated fish silage, used as an ingredient in animal feed and fertilization. The objective of this work was the development of the acidic silage of tambatinga (Colossoma macropomum X Piaractus brachypomus) and the application of the kinetics of drying in the product generated, in order to evaluate the interference of different temperatures in the physicochemical and microbiological composition. For the elaboration of silage, the use of tambatinga residue and the formulation of propionic and formic acids in the proportion of 1: 3, with addition of 3% of the volume, were used during a period of 10 days, where the pH and temperature were measured daily. Drying was applied at temperatures of 60 ° C and 70 ° C in a forced circulation oven. The samples were submitted to physico-chemical (moisture, protein, lipid and gray) and microbiological evaluations (mesophile, filamentous fungi and Salmonella). The results of the chemical composition showed high levels of moisture, lipids and ash, presenting significant differences between treatments, however, a reduction in protein concentration occurred in silage treatments, drying at 60 ° C and drying at 70 ° C when compared treatment of the raw material. The temperatures tested in the application of drying did not show significant differences, in relation to the results of the centesimal and microbiological composition, however, the temperature of 70 ° C stabilized in a shorter time